Балабақшаларда көптілділікті енгізу үшін Қостанай педагогикалық колледжінде кадр дайындау мəселесі - Тюлешова, Н.С.; Досмагамбетова, А.Б. (My University, 2016)
In this article is written the importance of polylingual education and given examples that what methods use the teachers in training specialists for inculcate the polylinguism in nursery schools.
Keywords: polylinguism; teacher; profession; pupil; education